2003
DOI: 10.1136/fn.88.6.f525
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion in infants and neonates: preliminary results obtained using dynamic susceptibility contrast enhanced magnetic resonance imaging

Abstract: Background: Previous studies have used the dynamic susceptibility contrast enhanced (DSCE) magnetic resonance (MR) imaging technique to measure cerebral perfusion in adults. Objective: To assess the feasibility of the technique in a heterogeneous cohort of sick human infants and identify cerebral perfusion abnormalities. Methods: Perfusion measurements were made by characterising the changing concentration of an injected bolus of contrast agent using a series of MR images acquired during the first pass of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…These findings are supported by a recent study that measured dynamic cerebral perfusion in premature as well as mature neonates compared with that of adults using susceptibility contrast enhancement magnetic resonance imaging techniques (21). The investigators observed that images of relative cerebral blood flow from mature infants were comparable to adults, whereas relative cerebral blood flow data in premature infants showed perfusion voids predominantly in white matter and well-detected perfusion in gray matter.…”
supporting
confidence: 75%
“…These findings are supported by a recent study that measured dynamic cerebral perfusion in premature as well as mature neonates compared with that of adults using susceptibility contrast enhancement magnetic resonance imaging techniques (21). The investigators observed that images of relative cerebral blood flow from mature infants were comparable to adults, whereas relative cerebral blood flow data in premature infants showed perfusion voids predominantly in white matter and well-detected perfusion in gray matter.…”
supporting
confidence: 75%
“…There have been fewer studies of DSC-MR imaging in children, and particularly neonates, than in adults. [56][57][58][59] Hand injections are preferred over power injections in infants, with less reproducibility. Wintermark et al 58 were the first to assess PWI in 5 term neonates with HIE on early (days 2-4) and late MR imaging (days 9 -11).…”
Section: Brain Perfusion Measurements By Using Mr Imagingmentioning
confidence: 99%
“…The pathophysiologic explanation for these different patterns remains unclear, but alterations of cerebral perfusion may be a major factor. Perfusionweighted imaging (PWI) has been used only occasionally in newborns so far (2)(3)(4). Furthermore, brain perfusion associated with these different patterns of neonatal encephalopathy has received little attention.…”
mentioning
confidence: 99%